A thermodynamic-based large deformation viscoplastic constitutive relationship for asphalt concrete compaction. (15th June 2019) - Karimi, Mohammad M.; Darabi, Masoud K.; Tabatabaee, Nader
Highlights: A large-deformation, thermodynamic-based constitutive relationship is proposed for asphalt concrete compaction. A viscoplastic constitutive relationship is derived within the thermodynamic framework. The proposed model properly represents the multi-axial state of stresses during compaction of asphalt concrete. The proposed model is calibrated against laboratory compaction experiments. The model substantially enhanced the prediction of asphalt concrete compaction in the lab and field. Abstract: This research proposes a large deformation, time-dependent viscoplastic constitutive relationship to enhance the prediction of the compaction degree of asphalt concrete materials under laboratory and field conditions. A large-deformation thermodynamic-based framework is presented. The Helmholtz free energy and rate of energy dissipation functions were assumed to derive rate-dependent constitutive relationships to relate multi-axial state of stresses to the recoverable and non-recoverable deformation response of asphalt concrete during compaction. A straightforward method that allows the calibration of the proposed model against laboratory compaction data (e.g., data from Superpave Gyratory Compactor; SGC) is presented. Numerical algorithms associated with the proposed constitutive relationship were implemented in the finite element (FE) code Abaqus via the user material subroutine UMAT. The model is calibrated against SGC deformation data at different number of gyrations (time). The calibrated model was utilized to predict the field compaction of asphalt concrete. Comparisons of the model predictions and field measurements showed that the model is capable of predicting the compaction of asphalt concrete materials both in the laboratory and in the field. Graphical abstract: Image, graphical abstract